Cohort profile of the Heidelberg study on diabetes and complications HEIST-DiC - Kliemank, Elisabeth; Rauchhaupt, Ekaterina von; Seebauer, Lukas; Roshan, Mani; Ansmann, Malin; Flegka, Viktoria; Schimpfle, Lukas; Tsilingiris, Dimitrios; Bartl, Hannelore; Fleming, Thomas; Kender, Zoltán; Jende, Johann; et al. (Scientific reports, 2025)
The Heidelberg Study on Diabetes and Complications (HEIST-DiC) is a prospective longitudinal study focused on the development and progression of diabetes-associated complications. Participants with/without diabetes mellitus undergo annual phenotyping of diabetes-associated complications over 11 years. Assessments include: albuminuria, estimated glomerular filtration rate for chronic kidney disease; clinical neuropathy scores, Purdue Pegboard test, electrophysiological examination, transcutaneous electrical nerve fiber stimulation, quantitative sensory testing and high-resolution magnetic resonance neurography for distal sensorimotor polyneuropathy; heart rate variability for cardiovascular autonomic neuropathy; funduscopic examination of undilated pupils for retinopathy; the 6-minute walk test, spirometry, body plethysmography, and carbon monoxide-based diffusing capacity measurements for respiratory lung disease; non-invasive scores, transient elastography and hepatic ultrasound for metabolic dysfunction-associated steatotic liver disease; ankle-brachial index and carotid intima-media thickness for peripheral atherosclerosis; hand grip strength for muscle function; bioelectrical impedance analysis for body composition; skin autofluorescence for measurement of advanced glycation end products. Beta-cell function and tissue-specific insulin sensitivity are evaluated using oral glucose tolerance test or euglycemic hyperinsulinemic clamp. The biobank stores specimens of blood, urine, skeletal muscle, subcutaneous adipose tissue, and skin. Health-related quality of life, physical health, and somatic and depression symptoms are measured via standardized questionnaires. HEIST-DiC explores diabetes onset in high-risk individuals, disease progression and the development of complications, aiming to design personalized strategies to prevent, mitigate, or reverse diabetes-related complications.
Online veröffentlicht: 12. August 2025
Gesehen am 09.01.2026